Thin-Layer Chromatographic Analysis of Steroids : A Review - Bhawani, Showkat Ahmad; Othman, Bin Sulaiman; Rokiah, Binti Hashim; Mohamad Nasir, Bin Mohamad Ibrahim (Pharmacotherapy Group, 2010)
Thin layer chromatography has been used for the analysis of natural and synthetic steroids in various environmental materials. This review focuses mainly on steroid analysis in environmental materials such as pharmaceuticals, plant products and other biological specimens. The most widely investigated biological specimens are urine and blood plasma or serum. Various chromatographic systems useful for the identification; separation and quantification of surfactants are also reported in this review.